Weight Gain and Body Composition Changes during the Transition of Thyroid Function in Patients with Graves’ Disease Undergoing Radioiodine Treatment - Zhenqin Cai; Qiyu Chen; Yan Ling (International Journal of Endocrinology)
Objective. This study aimed at investigating the dynamic changes in the body weight and body composition in a group of patients with Graves’ disease undergoing radioiodine therapy. Methods. Seventeen patients with Graves’ disease undergoing 131I treatment and forty-three euthyroid controls were recruited. Body weight, BMI, and body composition via bioelectrical impedance were measured for the participants at baseline, hypothyroid stage, and euthyroid stage. Results. Body weight increased significantly during the transition from hyperthyroidism to euthyroidism. However, there were no significant changes in body fat %, lean mass %, and bone mineral %. The body weight of 9 patients at the euthyroid stage exceeded their premorbid weight, while the remaining 8 patients’ weight did not exceed the premorbid weight. In the group with excessive weight gain, both body fat and lean mass increased significantly. However, in the group without excessive weight gain, only lean mass increased significantly. The patients with excessive weight gain had significantly higher body fat %, while lower lean mass % compared to patients without excessive weight gain at baseline and at the euthyroid stage. Moreover, body fat % of patients with excessive weight gain was significantly higher than that of controls, while lean mass % was significantly lower than that of controls. There was no difference of body fat % and lean mass % between patients without excessive weight gain and controls. Conclusion. 131I treatment caused significant weight gain in patients with Graves’ disease. An undesirable body composition at presentation may be a risk factor for excessive weight gain after hyperthyroidism treatment.